The Potential of Wind Energy and Design Implications on Wind Farms in Saudi Arabia - Naqash, Muhammad Tayyab; Aburamadan, Mohammad Hasan; Harireche, Ouahid; AlKassem, Abdulrahman; Farooq, Qazi Umar (International Journal of Renewable Energy Development, 2021)
Climate change and natural resource depletion are likely to affect the future economic development of a country. The generation of power from oil and gas is among the major causes of reserves depletion and global warming. However, renewable energy is also deemed a clean and green choice for power generation to promote sustainability in engineering. The coastal lines of the Kingdom of Saudi Arabia (KSA) are widely extended, and wind energy appears to be a viable alternative to traditional sources, which needs to be investigated as it is highly desirable to seek energy from renewable energy sources, for instance, wind. This paper is aimed at addressing the wind energy potential along the Red Sea coast of KSA. Afterward, a suitable wind turbine based upon careful structural analysis has been proposed, which would form a basis, especially during the machine selection and design phases. For this purpose, seven different sites located along the coastal line, namely: Al Wajh, Umluj, Yanbu, Rabigh, Jeddah, Haddad, and Gizan, were initially selected to assess the wind energy availability. After that, a suitable turbine is recommended for yielding maximum output. It has been found from the reconnaissance that Al Wajh has sufficient land availability that receives high perennial wind speed, alongside shallow offshore water depth for monopile installation. Hence, this site is recommended for the development of a wind farm. Furthermore, turbines need to be installed at the height of almost 100 m to produce maximum energy to appropriately utilize the available indigenous wind energy. It is pertinent to mention that the superstructure of the turbines is designed based on the local loading conditions (wind, currents, waves, etc.) of the Al Wajh region. Also, the monopile substructures are proposed in the selected area in accordance with the available bathymetry.